The Therapeutic Effect of Huo Xue Tong Luo Capsules in Association Research Circulation Osseous (ARCO) Stage II Osteonecrosis of the Femoral Head: A Clinical Study With an Average Follow-up Period of 7.95 Years - He, Xiao-Ming; He, Min-Cong; Yang, Peng; Zhang, Qing-Wen; Chen, Zhen-Qiu; He, Wei; Wei, Qiu-Shi (Frontiers in Pharmacology, 2021)
Abstract Background: Huo Xue Tong Luo (HXTL) capsules are an oral preparation that could relieve pain and ameliorate osteonecrosis in patients with asymptomatic Osteonecrosis of femoral head (ONFH). We wanted to verify whether it could be a treatment option for ARCO stage II ONFH. Methods: A total of 44 patients (66 hips) with ARCO stage II ONFH were recruited from June 1996 to October 2013 (clinical trial registry number: ChiCTR-RPC-15006290). HXTL capsules were given under a specific protocol, and the end point was set as femoral head collapse. The clinical indicators [including visual analog scale (VAS) and Harris Hip Score (HHS)] and radiological indicators [including Tonnis classification, ARCO stage, Japanese Investigation Committee (JIC) classification, lateral preserved angle (LPA), anterior preserved angle (APA), and combined preserved angle (CPA)] before and after treatment were compared. Kaplan–Meier survival analysis and Cox regression analysis were used to identify the risk factors associated with femoral head collapse. Result: Twenty-six males and 18 females with an average age of 38.3±2.8 were followed for an average of 7.95 years. Forty-six of the 66 (69.7%) hips had no progression in pain or collapse, patients exhibited a higher HHS (P<0.05) after therapy. Twenty of the 66 (30.3%) hips progressed in Tonnis classification and ARCO stage, but only 1 of the 66 (1.5%) hips required total hip arthroplasty (THA). The Kaplan–Meier survivorship curve suggested that the survival rates were 96.97% at 5 years, 69.15% at 10 years, and 40.33% at 15 years. Patients with type A necrotic lesions on anteroposterior (AP) and frog-leg lateral (FLL) radiographs revealed 100% survival rates. Multivariate Cox regression analysis revealed that patients with an LPA≤60.9°exhibited a 3.87 times higher risk of collapse of the femoral head [95% confidence interval (CI), 1.241-5.673] than did those patients with an LPA>60.9°. Conclusion: HXTL capsules could be a treatment option for ARCO stage II ONFH, resulting in improved hip function and delayed progression to femoral head collapse, especially when the anterior and lateral portions of the femoral head were not affected. However, an LPA of less than 60.9° may be a risk factor for collapse of the femoral head.